Hubungan Antara Persepsi Beban Kerja Dengan Kepuasan Kerja Pada Karyawan PT X - Ratna Puspita Ningrum; Ni Wayan Sukmawati Puspitadewi (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This research aims to determine the relationship between perceived workload and job satisfaction among PT. X. This research was conducted with a quantitative approach using correlational research. The population in this study were all permanent employees in the Quality Assurance & Quality Control (QAQC) Division of PT.X. Data collection in this research used product moment correlation. Based on the results of data analysis, there is a significant relationship between workload with job satisfaction whose correlation coefficient is -0.402 with a significant relationship of p=0.001. Negative values indicate an inverse relationship between two variables. The higher the perceived workload, the higher the workload the lower the job satisfaction of employees, and vice versa.